Competing intra- vs intermolecular nitrene transfer in the [Au]-catalysed reaction of 2-alkynylphenylazides - Dhote, Pawan S.; Ramana, V. Chepuri (Advanced Synthesis & Catalysis, 2022)
The possibility of interrupting the gold-catalysed intramolecular cyclization of 2-alkynylphenylazide derivatives, employing known nitrene transfer reagents such as anthranil and its isomer 1,2-benzisoxazole, has been attempted in search of developing simple tools for product diversification. With 1,2-benzisoxazoles, the intermolecular nitrene transfer leading to quinazoline is competitive with intramolecular azidoalkyne cyclization resulting in spiro indol-3-ylidene derivatives. However, in case of the reaction in the presence of anthranil, both intra- and intermolecular nitrene transfer processes result in the same product indol-3-ylidene.
Keywords: 2-Benzisoxazole; Anthranil and 1; Gold catalysis; Nitrene Transfer; Quinazoline